2021
DOI: 10.1108/medar-04-2020-0852
|View full text |Cite
|
Sign up to set email alerts
|

Internal audit functions, financial reporting quality and moderating effect of senior management support

Abstract: Purpose The purpose of this paper is to demonstrate the relationship between internal audit functions (IAF) and financial reporting quality (FRQ) and whether such a relationship is moderated by senior management support (SMS) in listed companies in Nigerian Stock Exchange (NSE). Design/methodology/approach This research is a cross-sectional study, using primary data in the form of a survey sent to 175 listed companies in NSE. A total of 149 questionnaires have been collected and analysed out of which 97 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 107 publications
(182 reference statements)
1
13
0
Order By: Relevance
“…One of the most significant role of the internal audit function is to prevent fraud and minimize the cost of unvaluable activities of the company (Church et al, 2001). Moreover, Madawaki et al (2022) found that internal audit qualities have a positive relationship with companies' work, internal control activities and higher coordination with the external auditor. Those findings are interpreted that a higher quality of internal audit function and stronger internal control of the company will achieve a better financial reporting quality.…”
Section: Literature Review and Hypothesis Development 21 Internal Aud...mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most significant role of the internal audit function is to prevent fraud and minimize the cost of unvaluable activities of the company (Church et al, 2001). Moreover, Madawaki et al (2022) found that internal audit qualities have a positive relationship with companies' work, internal control activities and higher coordination with the external auditor. Those findings are interpreted that a higher quality of internal audit function and stronger internal control of the company will achieve a better financial reporting quality.…”
Section: Literature Review and Hypothesis Development 21 Internal Aud...mentioning
confidence: 99%
“…Furthermore, The highlight of the critical role of the internal audit function inside of the company are found by several previous studies (Asare et al ., 2008; Azzam et al ., 2020; Church et al ., 2001; Madawaki et al ., 2022). One of the most significant role of the internal audit function is to prevent fraud and minimize the cost of unvaluable activities of the company (Church et al ., 2001).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The submission of audit findings and results of follow-up examinations, have the biggest role in fraud prevention through the creation of an honest culture, management's responsibility for evaluating risks and fraud, and supervision to eliminate opportunities for deception (Roszkowska & Melé, 2021). Improvements in internal auditing, such as independence, competence, scope of work and implementation of inspection activities, will increase fraud prevention in financial statements through reduced opportunities and reduced justification (Alleyne & Howard, 2005;Madawaki, Ahmi, & Ahmad, 2022).…”
Section: Effectiveness Of Internal Audit Functions and Preventing Fra...mentioning
confidence: 99%
“…According to the agency theory, the division of ownership and authority forces the agent to advance his own interests (Jensen and Meckling, 1976). An effective audit committee is established to supervise the financial reporting process in order to minimize such interests, which improves the caliber of financial reports (Madawaki et al, 2021;Chen and Komal, 2018). Additionally, the stakeholder theory of salience and identity (Mitchell et al, 1997) identifies a CEO as a significant internal stakeholder with the ability to affect the results of financial reporting.…”
mentioning
confidence: 99%